2006
DOI: 10.1002/app.24716
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of hydrophobically modified polyelectrolyte systems: Concentration effects

Abstract: The behavior of hydrophobically modified alkali‐soluble associative polymer (HASE) at various polymer concentrations was investigated. The results showed that the formation of network structure, which enhances the rheological behavior, depends on two critical polymer concentrations, namely the critical cluster overlapping concentration (C*) and the established network concentration (C**). C* is defined as the critical concentration for the transformation of individual cluster to a transient network structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Tam et al [118][119][120] superposed oscillatory shear and constant flow to probe the shear-induced structural changes of different HASE samples in the shear-thinning and shear-thickening regimes. They observed that with increasing applied stress, the junction density increased but the overall relaxation time of the system decreased.…”
Section: Polymers With Many Associative Groupsmentioning
confidence: 99%
“…Tam et al [118][119][120] superposed oscillatory shear and constant flow to probe the shear-induced structural changes of different HASE samples in the shear-thinning and shear-thickening regimes. They observed that with increasing applied stress, the junction density increased but the overall relaxation time of the system decreased.…”
Section: Polymers With Many Associative Groupsmentioning
confidence: 99%
“…These associative thickeners are applied in paint formulations, cosmetics and oil recovery. Other telechelic polymers, [8][9][10][11][12] triblock copolymers 13,14 or other molecular architectures [15][16][17][18][19][20][21] are based on the same mechanism and driving force. Some of this work is summarized in a recent review by Tsitsilianis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NPAM has higher surface activity than XG. Similar to the concept of critical micelle concentration (CMC), the concentration of the lower inflection point in the σ-c isotherm, that is, the point of transition to the asymptote of minimum surface tension, is often referred to as the critical polymer concentration (CPC) or critical cluster overlapping concentration (C*) 43,44 . As seen in Figure . 6, the critical polymer concentrations of NPAM and XG are estimated to be 10 g/m 3 and 50 g/m 3 , respectively.…”
Section: Surface Tensionmentioning
confidence: 99%